ATLANTIS IN SPAIN V - Papamarinopoulos, S.P (Bulletin of the Geological Society of Greece, 2010)
Following strictly Plato’s information we reach Iberia and there we discovered the basic geomorphological characteristics of a horseshow shape flat and elongated basin which is surrounded by mountains. The basin reaches the Atlantic Ocean. This valley is Andalusia and it was missed by Herodotus and Hecateus, who lived a century earlier than Plato, and constructed North West Europe’s map. The Iberian civilization is reflected in the Greek myths prior to Plato too. Atlantis’ catastrophe in the shape of the concentric scheme’s, being in Iberia’s coast, was realized by earthquakes and a tsunami. The discovery of the very first Mycenaean vase’s fragment, in Guadalquivir’s estuary by Spanish archaeologists in 1990, offered the first archaeological evidence that the prehistoric Greeks had visited Atlantis after all before the 12th century B.C. The recent interest of the Spanish Archaeological Survey in Andalusia initiated because it has been proved geologically that the region had not been submerged since the last ice age. New evidence suggests that the waters may have receded in time for the Iberians in the period Tartesssos to build an urban centre, which was later destroyed by earthquakes and a tsunami as Plato describes in Timaeos and Critias for this region. Although platonic Atlantis could not be considered, as Thucydides would prefer, a historical text but it cannot be considered as a single paramyth either since some parts of his text have been proved already. It can be considered as a genuine myth containing a true prehistoric kernel covered firstly by a layer of inventions produced by transmitting people, the story, from generation to generation between the actual occurrence of the event within the 12th century B.C. and Solon’s 6th century B.C. who recorded it and then of the 4th century B.C. when Plato wrote down. Atlantis is also covered by a platonic paramythical layer full of mathematics and musicological information which is recognized and can be removed liberating the genuine myth’s kernel from the platonic intervention.